EDUCATORS’ PERCEPTIONS REGARDING THE INCLUSION OF EXPERTS OF VARIOUS PROFILES INTO THE TEAM FOR INCLUSIVE EDUCATION (Heritage, 2021)
The past decade has witnessed the expansion of educators’ competencies and their larger concern for children with developmental delays, i.e. inclusive education. The inclusion of developmentally delayed children into education is determined by the following: early detection of developmental conditions, timely intervention, an individualized education plan (IEP) and its practical application. The IEP is developed and implemented by the inclusive education team. The team members responsible for the development of the IEP for children with developmental delays in regular preschool education are: parents or caregivers, teachers and educators, early childhood professionals, personal assistants for developmentally delayed children, special education teachers or dialectologists, pedagogical assistants and other professionals. The goal of this research was to determine educators’ opinion about the necessity of an early intervention as well as about the application of the IEP and the involvement of professional support in inclusive kindergarten programmes and practice. The sample was comprised of 70 early childhood educators with experience in teaching children with developmental delays. The research results showed that the participants were predominantly inclined towards the involvement of a music pedagogue into inclusive kindergarten education (51of them or 71%). Therefore, this paper analyses the possibilities of supporting children with developmental delays through music teaching classes.
Keywords: children with developmental delays, individualized approach, IEP